Identification of a Functional Homolog of the Yeast Copper Homeostasis Gene ATX1 from Arabidopsis - Himelblau, Edward (American Society of Plant Physiologists, 1998)
A cDNA clone encoding a homolog of the yeast (Saccharomyces cerevisiae) gene Anti-oxidant 1 (ATX1) has been identified from Arabidopsis. This gene, referred to as Copper CHaperone (CCH), encodes a protein that is 36% identical to the amino acid sequence of ATX1 and has a 48-amino acid extension at the C-terminal end, which is absent from ATX1 homologs identified in animals. ATX1-deficient yeast (atx1) displayed a loss of high-affinity iron uptake. Expression of CCH in the atx1 strain restored high-affinity iron uptake, demonstrating that CCH is a functional homolog of ATX1. When overexpressed in yeast lacking the superoxide dismutase gene SOD1, both ATX1 and CCH protected the cell from the reactive oxygen toxicity that results from superoxide dismutase deficiency. CCH was unable to rescue the sod1 phenotype in the absence of copper, indicating that CCH function is copper dependent. In Arabidopsis CCH mRNA is present in the root, leaf, and inflorescence and is up-regulated 7-fold in leaves undergoing senescence. In plants treated with 800 nL/L ozone for 30 min, CCH mRNA levels increased by 30%. In excised leaves and whole plants treated with high levels of exogenous CuSO(4), CCH mRNA levels decreased, indicating that CCH is regulated differently than characterized metallothionein proteins in Arabidopsis.